Tanzania’s Coffee Sector : Constraints and Challenges in a Global Environment - Baffes, John (World Bank, Washington, DC, 2012)
Coffee, Tanzania's largest export crop, contributes about 115 dollars to the country 's export earnings. About 95 percent of coffee is produced by some 400,000 smallholders on average plots of 1-2 hectares. Most do not use purchased inputs such as chemicals and fertilizers. Before 1990 all coffee marketing (including input provision, transportation, and processing) was handled by the state coffee board and the cooperative unions. Modest reforms were implemented in 1990 affecting inputs, price announcements, and retention of dollar export earnings. More comprehensive reforms were introduced beginning in 1994/95, allowing private traders to purchase coffee directly from growers and process it in their own factories for the first time in more than 30 years. While producers ' share of export prices increased, official statistics show no supply response. Coffee processing capacity, marketing efficiency, and investment in new plantings increased. Several issues remain to be addressed. Taxes should be consolidated, lowered, and rationalized across all export crops and other exports and the tax code should be simplified. Licensing procedures need to be reexamined. Licenses should be suspended only in accordance with the Coffee Industry Act of 2001, and not in response to requests by the cooperative unions or the Ministry of Cooperatives. The coffee auction should be voluntary, substantially reducing the costs of vertically integrated exporters and enhancing cross-border trade. The Tanzanian Coffee Board should be responsible for disseminating price and other information and for monitoring the quality of auction coffee sales and other coffee statistics. The power of the board and the ministry ought to be substantially reduced and their respective roles clearly defined.